Cushing, Penfield, and cortical stimulation - Leblanc, Richard (Journal of neurosurgery, 2019)
Harvey Cushing and Wilder Penfield enjoyed a unique professional and personal relationship. Shortly before his retirement from Harvard University in 1933, Cushing sent Penfield 8 sketches that he drew in 1902 and 1903 while he was at Johns Hopkins Hospital. The first series of 3 sketches illustrate the relationship between a cortical hemorrhagic lesion and the motor strip in a patient with focal motor seizures. The second series also comprises 3 sketches. These depict the operative findings in a patient in whom Cushing had electrically stimulated the precentral gyrus, before resecting the cortex subserving motility of the upper extremity to control painful dyskinetic movements. The third series consists of 2 sketches that illustrate the results of stimulation of the motor strip as an aid in the safe resection of an epileptogenic focus in a patient with Jacksonian seizures. These sketches are the subjects of this paper. They add to the relatively sparse record of Cushing's activities in cortical stimulation and in the treatment of functional disorders.